Immediate-term effects of use of an ankle–foot orthosis with an oil damper on the gait of stroke patients when walking without the device. (April 2015) - Yamamoto, Sumiko; Ibayashi, Setsuro; Fuchi, Masako; Yasui, Tadashi
Background: An ankle–foot orthosis using an oil damper is designed to enable natural movement of the ankle joint. Wearing an ankle–foot orthosis using an oil damper has been demonstrated to assist the first rocker in stroke patients, but its effect on their gait when not wearing it is unclear. Objectives: To determine the effect of use of ankle–foot orthosis using an oil damper on the gait of stroke patients with hemiparesis when not wearing the ankle–foot orthosis. Study design: Crossover study. Methods: The gait of eight stroke patients in the chronic phase when not wearing an ankle–foot orthosis was measured, using a three-dimensional motion analysis system, before using the ankle–foot orthosis using an oil damper and then without and with using the ankle–foot orthosis using an oil damper after 3 weeks of use. Differences in gait were compared between the three measurement conditions. Results: Use of ankle–foot orthosis using an oil damper significantly decreased preswing time and significantly increased the positive ankle joint power in stance when not wearing the ankle–foot orthosis using an oil damper. Conclusions: These changes indicate the promising therapeutic effects of ankle–foot orthosis using an oil damper use and suggest the ankle–foot orthosis using an oil damper's potential as a therapeutic device. Clinical relevance: After 3 weeks of use of an ankle–foot orthosis using an oil damper, which assists the first rocker, the gait of stroke patients in the chronic phase when not wearing the ankle–foot orthosis using an oil damper was improved. Preswing time was significantly decreased and positive ankle joint power was significantly increased. The ankle–foot orthosis using an oil damper, which assists the first rocker function with natural movement of the ankle joint during gait, has the potential to improve the gait of stroke patients after immediate-term use.